Odor removal catalyst and its uses

JP7645284B2Active Publication Date: 2025-03-13MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022567020
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-04
Filing Date
2021-12-06
Publication Date
2025-03-13
Estimated Expiration
2041-12-06

AI Technical Summary

Benefits of technology

【0014】 本発明の臭い除去触媒は、安全性が高く、臭気成分を吸着し、吸着した臭気成分を分解することにより、温度上昇等に伴って一度吸着した臭気成分を放出する問題を生じることなく、長期間持続的に臭いを低減することができる。本発明の臭い除去触媒は、臭気を有する空間に設置することで、長期間継続的に臭いを低減することができ、自動車等の車内、室内等を効果的に脱臭することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645284000012
    Figure 0007645284000012
  • Figure 0007645284000013
    Figure 0007645284000013
  • Figure 0007645284000014
    Figure 0007645284000014
Patent Text Reader

Abstract

Provided are: an odor removal catalyst comprising at least one first metal element selected from the group consisting of Ru, Rh, Pd, Os, Ir, and Pt, at least one second metal element selected from the group consisting of Al, Si, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, La, and Sm, and an oxide of Ce, wherein the proportion of the Ce atom with respect to all the metal atoms is at least 15 mol%; a deodorizer composition and a deodorization product which use said odor removal catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an odor removing catalyst and its use. [Background technology]

[0002] Various odors occurring in the environment (exhaust gas, odors from garbage and food, odors emitted from newly built houses and buildings, etc.) are major social issues, and effective countermeasures are required for each environment. In particular, odors in closed spaces such as homes, public facilities such as hotels and restaurants, and transportation facilities such as trains and automobiles are problematic, but since people coexist, it is difficult to install special equipment (ozone deodorization, hypochlorous acid deodorization, etc.) that has safety concerns, and easy-to-use adsorbents are preferably used. However, if the adsorbent is used continuously, it will exceed its adsorption capacity and break through, so it needs to be replaced frequently. In addition, especially on days when the temperature is high, it is problematic that odorous components that have been adsorbed once are released from the adsorbent, generating a foul odor.

[0003] As a technology for adsorbing and decomposing odorous components in the air, for example, Patent Document 1 discloses a gas removal material made of a composite oxide containing ruthenium and at least two or more transition base metal elements, and describes that this gas removal material has excellent ability to remove odorous and harmful gases under normal temperature and humidity conditions. Patent Document 2 discloses an aldehyde removal catalyst which is a composite metal catalyst containing cerium and copper, and contains 4 to 20 mass % of copper in terms of CuO in the composite metal catalyst. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-159315 A [Patent Document 2] JP 2017-94309 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the aldehyde removal catalysts and the like in the above-mentioned prior art have room for further improvement in odor removal ability. Therefore, an object of the present invention is to provide an odor removal catalyst that can quickly adsorb and remove odors in spaces such as the inside of an automobile, and by decomposing the adsorbed odorous components, can reduce odors sustainably over a long period of time and prevent odor return, and to provide a deodorant composition and a deodorant product that use the odor removal catalyst. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted intensive research in light of the above-mentioned circumstances and have found that the above-mentioned problems can be solved by using a catalyst containing an oxide of a specified metal element, thereby completing the present invention. The present invention relates to, for example, the following items [1] to

[10] .

[0007] [1] At least one first metallic element selected from the group consisting of Ru, Rh, Pd, Os, Ir and Pt; At least one second metallic element selected from the group consisting of Al, Si, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, La and Sm, and Ce wherein the ratio of Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element and Ce atoms is 15 mol % or more.

[0008] [2] The odor removal catalyst of [1], wherein the first metal element is Ru and the second metal element is Cu.

[0009] [3] The odor removal catalyst of [1] or [2], wherein the ratios of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms are 0.05 to 75 mol %, 5 to 79.95 mol % and 18 to 94.95 mol %, respectively.

[0010] [4] The odor removal catalyst according to [3] above, wherein a ratio of atoms of the first metal element to a total of atoms of the first metal element, atoms of the second metal element and Ce atoms is 0.05 to 10 mol %.

[0011] [5] A deodorant composition comprising the odor removing catalyst according to any one of [1] to [4] above and a chemical adsorbent. [6] A deodorizing product comprising the odor removing catalyst according to any one of [1] to [4] above or the deodorant composition according to [5] above.

[0012] [7] The deodorizing product according to [6] above, which is a deodorizing fiber, a deodorizing paint or a deodorizing sheet. [8] The deodorizing product according to [6] or [7] above is used for upholstery, curtains, carpets, tiles, wallpaper, air filters, or interior materials for vehicles.

[0013] [9] An antibacterial and antiviral deodorizing product comprising the odor removal catalyst according to any one of [1] to [4] above or the deodorant composition according to [5] above.

[10] The antibacterial and antiviral deodorizing product according to [9] is used for upholstery, curtains, carpets, tiles, wallpaper, air filters, or interior materials for vehicles. Effect of the Invention

[0014] The odor removal catalyst of the present invention is highly safe, and by adsorbing odorous components and decomposing the adsorbed odorous components, it is possible to reduce odors continuously for a long period of time without the problem of releasing the odorous components once adsorbed due to an increase in temperature, etc. By installing the odor removal catalyst of the present invention in a space containing an odor, it is possible to reduce odors continuously for a long period of time, and it is possible to effectively deodorize the interior of a vehicle, etc., or a room, etc.

[0015] The odor removing catalyst of the present invention can be used as a deodorant as it is, and can also be used in various forms such as compositions containing the same, resin coating materials, interior sheet materials, and automobile inner panels as a component that provides an odor removing effect. According to the present invention, by using the odor removing catalyst of the present invention and products containing the same, odorous substances such as aldehydes, carboxylic acids, and esters can be suitably decomposed and removed. Furthermore, according to the present invention, it is possible to provide an odor removing method that can safely and sustainably decompose and remove odorous substances for a long period of time. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a graph showing the change in propionaldehyde concentration over time in a propionaldehyde continuous decomposition test of the odor removal catalyst obtained in Example 1. [Diagram 2] FIG. 2 is a graph showing the change in carbon dioxide concentration over time during a propionaldehyde continuous decomposition test of the odor removal catalyst obtained in Example 1. [Diagram 3] FIG. 3 is a graph showing the change in ethyl acetate concentration over time in a test of continuous decomposition of ethyl acetate using the odor removal catalyst obtained in Example 1. [Figure 4] FIG. 4 is a graph showing the change in carbon dioxide concentration over time during a continuous decomposition test of ethyl acetate using the odor removal catalyst obtained in Example 1. [Diagram 5] FIG. 5 is a graph showing the relationship between odorant concentration and odor intensity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] <Odor removal catalyst> The odor removing catalyst of the present invention is At least one first metallic element selected from the group consisting of Ru (ruthenium), Rh (rhodium), Pd (palladium), Os (osmium), Ir (iridium) and Pt (platinum); At least one second metallic element selected from the group consisting of Al (aluminum), Si (silicon), Sc (scandium), Ti (titanium), V (vanadium), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Cu (copper), Zn (zinc), Y (yttrium), La (lanthanum) and Sm (samarium), and Ce (Cerium) and a ratio of Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element and Ce atoms is 15 mol % or more.

[0018] The first metal element is a noble metal element such as Ru that exhibits a high oxidizing effect, and the second metal element is an element that contributes to the dispersion of the first metal element in the oxide particles. Among the second metal elements, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Zn are transition metal elements (Zn is also included in the transition metal elements) that are easily changed in valence, and promote the change in valence of Ce, thereby promoting the generation of oxygen defects in the oxide crystal. Due to the presence of oxygen defects, the oxide of the first metal element (only) is stabilized even in small particles, and is highly dispersed in the oxide particles of Ce and the second metal element. Among the second metal elements, Sc, Y, La, and Sm, which belong to rare earths, are easily dissolved in Ce oxide, and promote the generation of oxygen defects, thereby contributing to the high dispersion of the first metal element. Furthermore, among the second metal elements, Al and Si contribute to the high dispersion of the first metal element because their oxides have a high specific surface area. It is presumed that the second metal element functions in this way.

[0019] Therefore, it is presumed that the odor removal catalyst of the present invention exhibits good odor removal performance similar to the odor removal catalyst of the examples in which composite oxides of Ru, Cu, Ce, etc., as described below, are used.

[0020] The first metal element is at least one selected from the group consisting of Ru, Rh, Pd, Os, Ir and Pt, preferably at least one selected from the group consisting of Ru, Rh and Pd, and more preferably Ru.

[0021] The second metal element is at least one selected from the group consisting of Al, Si, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, La and Sm, for example, at least one selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn, at least one selected from the group consisting of Sc, Y, La and Sm, or at least one selected from the group consisting of Al and Si, preferably at least one selected from the group consisting of Al, Si, Fe, Co, Ni, La and Cu (for example, at least one selected from the group consisting of Fe, Co, Ni and Cu), and more preferably Cu.

[0022] Examples of the oxide include a mixture of an oxide of the first metal element, an oxide of the second metal element, and an oxide of Ce (hereinafter also referred to as an "oxide mixture"), and a composite oxide of the first metal element, the second metal element, and Ce. Among these, the composite oxide is preferable. Although the detailed structure of the composite oxide is not necessarily clear, the composite oxide may include, for example, an oxide containing Ce in which the first metal element or the second metal element is solid-dissolved, an oxide particle of the first metal element is dispersed in an oxide particle of Ce and the second metal element, and the like.

[0023] The oxide mixture is preferably a mixture of an oxide of the first metal element, which is at least one selected from the group consisting of Ru, Rh and Pd, an oxide of the second metal element, which is at least one selected from the group consisting of Al, Si, Fe, Co, Ni, La and Cu (e.g., at least one selected from the group consisting of Fe, Co, Ni and Cu), and an oxide of Ce, and is more preferably a mixture of an oxide of Ru, an oxide of Cu and an oxide of Ce.

[0024] The composite oxide is preferably a composite oxide of the first metal element, which is at least one selected from the group consisting of Ru, Rh, and Pd, the second metal element, which is at least one selected from the group consisting of Al, Si, Fe, Co, Ni, La, and Cu (e.g., at least one selected from the group consisting of Fe, Co, Ni, and Cu), and Ce, and is more preferably a composite oxide of Ru, Cu, and Ce.

[0025] The ratio of Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element, and Ce atoms in the oxide is 15 mol% or more. When the ratio of Ce is within this range, an odor removal catalyst with good odor removal performance can be obtained. On the other hand, when this ratio is less than 15 mol%, the removal performance of the obtained odor removal catalyst is inferior.

[0026] The proportions of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms in the oxide are, based on the above criteria, i.e., relative to the total of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms in the oxide, preferably 0.05 to 75 mol %, 5 to 79.95 mol %, and 18 to 94.95 mol %, respectively, more preferably 0.05 to 10 mol %, 5 to 75 mol %, and 18 to 85 mol %, respectively, and even more preferably 0.05 to 7 mol %, 15 to 75 mol %, and 20 to 84.95 mol %, respectively.

[0027] The oxide may contain the first metal element having different valences (e.g., Ru(III) and Ru(IV)), the second metal element having different valences (e.g., Cu(I) and Cu(II)), and Ce having different valences (e.g., Ce(III) and Ce(IV)).

[0028] The specific surface area of ​​the odor removal catalyst of the present invention measured by the BET method is, for example, 50 to 500 m 2 / g, preferably 100 to 300m 2 / g. This specific surface area can be adjusted, for example, by pulverizing the odor removing catalyst.

[0029] The odor removal catalyst of the present invention has an excellent deodorizing effect, and can particularly suitably reduce and remove odorous substances such as aldehydes, carboxylic acids, esters, etc. Specifically, at least a portion of the odorous substances in the surrounding gas that comes into contact with the odor removal catalyst of the present invention is decomposed, and as a result, the odorous substances can be reduced and removed.

[0030] The odor removal catalyst of the present invention is unlikely to cause the problem of releasing odorous substances and diffusing odors even when exposed to high temperatures, and since the adsorbed odorous substances are decomposed and diffused, the adsorption capacity does not decrease significantly, and the catalyst can be used for deodorization for a long period of time.

[0031] <Method of manufacturing odor removal catalyst> A method for producing an odor removal catalyst containing the oxide mixture according to the present invention includes a method comprising a step of mixing an oxide of the first metal element (e.g., ruthenium oxide), an oxide of the second metal element (e.g., copper oxide) and an oxide of Ce.

[0032] The ratio of Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element, and Ce atoms contained in these oxides is 15 mol% or more. When the ratio of Ce is within this range, an odor removal catalyst with good odor removal performance can be obtained. On the other hand, when this ratio is less than 15 mol%, the removal performance of the obtained odor removal catalyst is inferior.

[0033] These oxides are mixed so that the ratio of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms in the odor removal catalyst according to the present invention is the above-mentioned ratio. The oxide is preferably in the form of a powder or particles.

[0034] The method for producing an odor removal catalyst containing the composite oxide according to the present invention includes, for example, A step (1) of dissolving the salt of the first metal element, the salt of the second metal element, and the salt of Ce in a solvent (preferably water) capable of dissolving the salts to prepare a solution (preferably an aqueous solution); (2) mixing the solution with a base to form a precipitate and prepare a slurry; (3) obtaining a catalyst precursor from the slurry; and and (4) calcining the catalyst precursor to produce an odor removal catalyst.

[0035] Examples of the salt used in step (1) include chlorides, bromides, nitrates, sulfates, and acetates of the first metal element, the second metal element, or Ce, and preferably chlorides, nitrates, and acetates. These may be hydrates. Specific examples of the salt include ruthenium(III) chloride, copper(II) nitrate trihydrate, and cerium(III) nitrate hexahydrate.

[0036] The solution may or may not further contain an oxide of one or more elements selected from the group consisting of the first metal element, the second metal element, and Ce. These oxides may be added to the solvent when dissolving the salt of the first metal element, the salt of the second metal element, and the salt of Ce in the solvent, or may be mixed with the prepared solution. Examples of the oxides include oxides of the first metal element such as ruthenium oxide, oxides of the second metal element such as copper oxide, and cerium oxide. The oxides are preferably in the form of powder or particles.

[0037] The ratio of Ce atoms to the total of the atoms of the first metal element, the atoms of the second metal element, and Ce atoms contained in these salts and any oxides is 15 mol% or more. When the ratio of Ce is within this range, an odor removal catalyst with good odor removal performance can be obtained. On the other hand, when this ratio is less than 15 mol%, the removal performance of the obtained odor removal catalyst is inferior.

[0038] The proportions of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms contained in these salts and any oxides based on the above criteria are preferably 0.05 to 75 mol %, 5 to 79.95 mol %, and 18 to 94.95 mol %, respectively, more preferably 0.05 to 10 mol %, 5 to 75 mol %, and 18 to 85 mol %, respectively, and even more preferably 0.05 to 7 mol %, 15 to 75 mol %, and 20 to 84.95 mol %, respectively, based on the total of the atoms of the first metal element, the atoms of the second metal element and the Ce atoms contained in these salts and any oxides.

[0039] Examples of the base used in step (2) include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, ammonia, and urea. These may be in the form of a solution (preferably an aqueous solution). The slurry obtained in step (2) is preferably stirred.

[0040] In step (3), a catalyst precursor is obtained from the slurry obtained in step (2). The catalyst precursor may be a solid fraction recovered from the slurry (by means of filtration or the like) or may be a solid fraction prepared by subjecting the slurry to hydrothermal synthesis, preferably the latter. This hydrothermal synthesis is carried out, for example, at 80 to 300°C for 5 to 48 hours. The catalyst precursor is preferably washed with distilled water and then dried by heating.

[0041] The firing in step (4) is carried out, for example, at 120 to 600° C. for 1 to 48 hours. The firing is preferably carried out in an oxygen-containing atmosphere, for example, under air flow. The odor removing catalyst obtained by calcination may be used as it is or may be pulverized before use.

[0042] The method for producing the odor removing catalyst according to the present invention further includes the steps of: A step (11) of dissolving the salt of the first metal element and the salt of the second metal element in a solvent (preferably water) in which the salts are soluble to prepare a solution (preferably an aqueous solution); A step (12) of dispersing cerium oxide in the solution to prepare a dispersion; A step (13) of removing the solvent from the dispersion to obtain a solid content; and and a step (14) of calcining the solid to produce an odor removal catalyst.

[0043] The details of the salt of the first metal element and the salt of the second metal element used in step (11) are the same as those of the salts used in step (1) described above. The cerium oxide used in step (12) is preferably in the form of a powder or particles.

[0044] An example of a method for removing the solvent in the step (13) is to heat the dispersion to evaporate the solvent. The calcination conditions in step (14) are the same as those in the above-mentioned step (4). The odor removing catalyst obtained by calcination may be used as it is, or may be crushed before use.

[0045] <Deodorant composition> The odor removing catalyst of the present invention may be used alone or in combination with other (additional) components. For example, it can be used as a deodorant composition containing the odor removing catalyst of the present invention and other (additional) odor removing components that remove, neutralize or decompose odorous components.

[0046] As the other odor removing component, any known one can be used without any restrictions, but it is preferable to use a chemical adsorbent. In particular, by mixing a chemical adsorbent that deodorizes by chemical interaction with odorous substances with the odor removing catalyst according to the present invention described above, a deodorant composition with particularly improved initial performance can be obtained. Examples of chemical adsorbents include Toagosei's Kesmon NS-750 (organic amine-supported silica; for aldehydes), NS-70 (Ca, Mg-based compounds; for acids), NS-10 (zirconia phosphate; for ammonia), and NS-20C (Cu-based compounds supported silica; for sulfur compounds); Otsuka Chemical's ChemCatch (adipic acid dihydrazide; for aldehydes); and Synacene Zeomic's Dashlight S (amine compound-supported silica; for aldehydes). The ratio of other odor removing components in the deodorant composition may be, for example, 1 to 50 parts by mass per 100 parts by mass of the odor removing catalyst according to the present invention.

[0047] <Deodorizing products> The deodorizing product of the present invention contains the odor removing catalyst of the present invention or the deodorizing composition of the present invention. The odor removing catalyst of the present invention (when the odor removing catalyst is used in the form of a deodorant composition, it is a deodorant composition; hereinafter referred to as "odor removing catalyst and deodorant composition") can be appropriately prepared into a deodorant product such as a liquid, solid, or gel-like solid by known methods, and can be used for various deodorant applications for industrial and household use. Examples of deodorant liquids include liquids in which the odor removal catalyst or deodorant composition of the present invention is suitably dissolved in water or an organic solvent such as ethanol, or liquids in which the odor removal catalyst or deodorant composition of the present invention is suitably emulsified with a surfactant, or aerosol deodorants in which such liquids are filled in a spray container together with a propellant. Examples of deodorizing solid agents include powder agents in which the odor removal catalyst or deodorizing composition of the present invention is mixed with powdered inorganic substances such as silica or perlite, those in which the catalyst or deodorizing composition is adsorbed on paper or porous substances, or those in which the catalyst or deodorizing composition is kneaded into synthetic resins such as polyethylene. Examples of gel-like solid deodorants include those in which the odor removing catalyst or deodorant composition of the present invention is added to a natural or synthetic polymer gel base such as agar, carrageenan, polyethylene glycol, etc. Furthermore, surfactants, bactericides, fragrances, colorants, etc. may be appropriately added to these formulations as necessary.

[0048] The deodorizing product of the present invention can be used for home use, for example, to deodorize rooms, refrigerators, toilets, trash cans, etc., and to remove and prevent body odor, and can also be used for industrial use, for example, to remove odors in sewage treatment plants, fish processing plants, fish meal manufacturing plants, livestock barns, livestock or chicken manure drying sites, pulp factories, etc.

[0049] One of the useful deodorizing products using the odor removing catalyst and deodorant composition of the present invention is a deodorizing fiber. In this case, the odor removing catalyst and deodorant composition may be attached or adhered to the surface of the raw fiber (1), or the odor removing catalyst and deodorant composition may be embedded in the raw fiber so as to be exposed on the surface of the raw fiber (2). The raw fiber may be either natural or synthetic fiber, and may be any of short fiber, long fiber, and composite fiber having a core-sheath structure. The deodorizing fiber (1) can be obtained by applying a deodorizing agent-containing liquid composition (coating liquid) (hereinafter, simply referred to as "coating liquid") consisting of an aqueous or organic solvent-based suspension containing an odor removing catalyst and a deodorizing agent composition to the surface of the raw fiber by a method such as gravure coating, dipping, or spray coating, and then removing the medium such as the solvent.

[0050] The deodorant-containing liquid composition (coating liquid) may contain a binder for improving the adhesive force of the deodorant composition to the surface of the raw fiber. Examples of the binder include acrylic binders, acrylic silicone binders, styrene binders, and acrylic styrene binders. The ratio of the deodorant-containing liquid composition (coating liquid) to the binder (total mass of components other than the binder in the deodorant-containing liquid composition (coating liquid) / mass of the binder) is, for example, 95 / 5 to 10 / 90, preferably 90 / 10 to 30 / 70, and more preferably 80 / 20 to 40 / 60. The lower the binder ratio, the easier it is to exhibit the deodorant's performance, but the easier it is to fall off from the fibers. It is necessary to select an appropriate ratio depending on the application.

[0051] When the viscosity of the deodorant-containing liquid composition is low and the deodorant composition settles, a thickener can be added. Examples of thickeners include polysaccharides such as sodium alginate, methyl cellulose, hydroxypropyl cellulose, and xanthan gum, polyvinyl alcohol, and polymethacrylic acid-based thickeners. The thickener is added to the coating liquid in an amount of, for example, 0.01 to 10% by mass, preferably 0.1 to 5% by mass, and more preferably 0.2 to 2% by mass.

[0052] If the wettability of the coating liquid to the raw material fibers is insufficient, a surfactant may be added. Examples of the surfactant include sodium alkylbenzenesulfonate, sodium alkyloxybenzenesulfonate, sodium alkyl sulfate such as sodium lauryl sulfate, and acetylene glycol surfactants. The surfactant is added to the coating liquid in an amount of, for example, 0.01 to 10% by mass, preferably 0.1 to 5% by mass, and more preferably 0.2 to 2% by mass. The pH of the aqueous coating liquid containing the deodorant composition is not particularly limited, but is preferably around 6 to 8 in order to fully exhibit the performance of the deodorant composition.

[0053] The deodorizing fiber (2) can be obtained by blending the odor removing catalyst and the deodorant composition of the present invention with a melt or a dissolved fiber resin solution of a liquid fiber resin, and fiberizing the obtained deodorant-containing resin composition. The fiber resin that can be used in this method is not particularly limited, and known chemical fibers can be used. Preferred resins are polyester, polyamide, acrylic, polyethylene, polypropylene, polyvinyl, polyvinylidene, polyurethane, polystyrene, etc. These resins may be homopolymers or copolymers. In the case of copolymers, the polymerization ratio of the monomers is not particularly limited.

[0054] The ratio of the odor removing catalyst and the deodorant composition contained in the deodorant-containing resin composition is not particularly limited.In general, if the content of the odor removing catalyst and the deodorant composition is increased, the deodorant property can be exerted strongly and can be sustained for a long time, but even if it is contained more than a certain amount, there is no big difference in the deodorant effect, or the strength of the deodorant fiber may decrease, so the ratio of the odor removing catalyst and the deodorant composition is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the fiber resin.

[0055] Another major deodorant product of the odor removing catalyst and deodorant composition of the present invention is a deodorant-containing paint composition. When producing a deodorant-containing paint composition, the oil or resin that is the main component of the paint vehicle used is not particularly limited, and may be any of natural vegetable oils, natural resins, semi-synthetic resins and synthetic resins. Examples of the oil and resin that can be used include drying oils or semi-drying oils such as linseed oil, linseed oil and soybean oil, rosin, nitrocellulose, ethylcellulose, cellulose butyrate, benzylcellulose, novolac-type or resol-type phenolic resins, alkyd resins, aminoalkyd resins, acrylic resins, vinyl chloride resins, silicone resins, fluororesins, epoxy resins, urethane resins, saturated polyester resins, melamine resins and polyvinylidene chloride resins. The deodorant-containing paint composition may be either thermoplastic or curable.

[0056] The ratio of the odor removing catalyst and the deodorant composition of the present invention contained in the deodorant-containing paint composition is not particularly limited. In general, if the content of the odor removing catalyst and the deodorant composition is increased, the deodorant effect can be exerted strongly and can be sustained for a long time, but even if it is contained more than a certain amount, there is no significant difference in the deodorant effect, or the painted surface loses its gloss or cracks. Therefore, the content of the odor removing catalyst and the deodorant composition is preferably 0.1 to 20 mass%, more preferably 0.5 to 10 mass%, based on 100 mass% of the deodorant-containing paint composition.

[0057] The odor removing catalyst and deodorant composition of the present invention can be used for both liquid paints and powder paints. The deodorant-containing paint composition may be of a type that forms a film by any mechanism, and when the coating film is cured, it may be of an oxidation polymerization type, a moisture polymerization type, a heat curing type, a catalyst curing type, an ultraviolet curing type, or a polyol curing type. It may also be applied to sintered coating that is cured by baking. The pigment, dispersant, and other additives that are blended in the composition are not particularly limited, except for those that may chemically react with the odor removing catalyst and deodorant composition of the present invention. The deodorant-containing paint composition can be easily prepared, and specifically, the raw material components may be sufficiently dispersed and mixed using a general mixing device such as a ball mill, a roll mill, a disperser, or a mixer.

[0058] Further, another deodorizing product using the odor removing catalyst and deodorant composition of the present invention is a deodorizing sheet (including a deodorant film). The raw material sheet before processing is not particularly limited, and its material, fine structure, etc. can be made according to the application, etc. Preferred materials for the raw material sheet are organic materials such as resin and paper, inorganic materials, or composites thereof. Raw material sheets that have air permeability from one side to the other side are preferably used. Other preferred examples of the raw material sheet include Japanese paper, synthetic paper, nonwoven fabric, resin film, etc., and a particularly preferred raw material sheet is paper made of natural pulp and / or synthetic pulp. When natural pulp is used, deodorant particles are easily sandwiched between finely branched fibers, and it can become a practical carrier even without using a binder. On the other hand, synthetic pulp has the advantage of excellent chemical resistance. When synthetic pulp is used, it may be difficult to support the deodorant particles by sandwiching the powder between the fibers, so in order to prevent this, a part of the fiber may be melted in the drying process after papermaking to increase the adhesive force between the powder and the fiber, or another thermosetting resin fiber may be mixed into a part of the fiber. By mixing natural pulp and synthetic pulp in an appropriate ratio, paper with various adjusted properties can be obtained, but generally, by increasing the ratio of synthetic pulp, paper with excellent strength, water resistance, chemical resistance, oil resistance, etc. can be obtained, while by increasing the ratio of natural pulp, paper with excellent water absorption, gas permeability, hydrophilicity, moldability, texture, etc. can be obtained.

[0059] The deodorizing sheet may be one in which the deodorizing agent composition is contained throughout the entirety of the raw material sheet from one side to the other side, or may be disposed in a surface layer on one or the other side, or may be disposed inside the raw material sheet excluding the surface layer.

[0060] The amount of the odor removing catalyst and the deodorant composition of the present invention contained in the deodorant sheet is not particularly limited. In general, if the amount of the odor removing catalyst and the deodorant composition is increased, the deodorant effect can be strongly exerted and can be sustained for a long time, but even if it is carried beyond a certain level, there is no significant difference in the deodorant effect. Therefore, the amount of the odor removing catalyst and the deodorant composition carried is preferably 0.1 to 10 parts by mass per 100 parts by mass of the raw material sheet.

[0061] The method for producing the deodorant sheet is not particularly limited. The odor removing catalyst and deodorant composition of the present invention may be supported either simultaneously with the production of the raw material sheet or after the production of the raw material sheet. For example, when supported on paper, a method of introducing the odor removing catalyst and deodorant composition in any step of the papermaking process, or a method of applying, immersing or spraying a deodorant-containing liquid composition (coating liquid) containing a binder onto previously produced paper can be applied. The type of binder, thickener and surfactant that can be added to the coating liquid are the same as those explained in the section on deodorant fibers. When a deodorant-containing liquid composition is used, the amount of the odor removing catalyst and deodorant composition supported is 0.05 to 10 g / m 2 It is preferable to coat the film so that the thickness becomes approximately 1 / 2 mm.

[0062] <How to remove odor> The odor removing method of the present invention is a method for reducing and removing odors caused by odorous substances using the odor removing catalyst of the present invention described above or a deodorant composition or deodorant product containing the same (hereinafter also referred to as "odor removing catalyst, etc."), for example, a method for reducing odors caused by at least one odorous substance selected from aldehydes, carboxylic acids, esters, amines, thiols, and hydrocarbons, preferably at least one odorous substance selected from aldehydes, carboxylic acids, and esters. The odor removing catalyst may be used as it is, or may be used in combination with other materials.

[0063] The odor removal method of the present invention can be achieved by contacting the above-mentioned odor removal catalyst etc. of the present invention with a gas from which the odor is to be removed (a gas containing odorous substances).Specific examples of the odor removal method include placing the odor removal catalyst etc. of the present invention in a space from which the odor is to be removed, and ventilating a gas containing odorous substances into a space in which the odor removal catalyst etc. of the present invention is present.

[0064] When odors are removed using the odor removing catalyst etc. of the present invention, the adsorbed odorous substances are not released and the adsorption capacity is restored, so odors caused by odorous substances can be reduced and removed for a long period of time. In addition, when a deodorant composition or deodorant product containing a chemical adsorbent that eliminates odors by chemical interaction with odorous substances is used together with the odor removing catalyst of the present invention, the initial odor reduction effect can be further improved.

[0065] <Application> As described above, the odor removing catalyst of the present invention and the deodorant composition and deodorant product containing the same can reduce and remove odors for a long period of time by adsorbing and decomposing surrounding odorous substances, and can particularly reduce and remove odors caused by odorous substances selected from aldehydes, carboxylic acids, esters, amines, thiols, and hydrocarbons, preferably at least one odorous substance selected from aldehydes, carboxylic acids, and esters. In addition, the odor removing catalyst of the present invention and the deodorant composition and deodorant product containing the same have antibacterial and antiviral properties, and are particularly excellent in antibacterial properties, so they can be suitably used in applications where antibacterial and antiviral properties are required for the surface of a product, etc.

[0066] The odor removal catalyst of the present invention and the deodorant composition containing the same can be suitably used to reduce and remove odors caused by odorous substances in the air, and can be particularly suitably used for deodorizing indoor spaces such as the inside of an automobile. Furthermore, the odor removing catalyst, deodorant composition and deodorant product of the present invention can be applied to various uses without particular limitation, for example, upholstery, curtains, carpets, tiles, wallpaper, interior materials for vehicles, etc. For these uses, any form of the deodorant product described above may be used.

[0067] Examples of vehicles for which the vehicle interior is used include automobiles, trains, passenger planes, and ships. Examples of vehicle interior materials include ceiling materials, inner panels, door trims, headrests, steering wheels, shift levers, instrument panels, seat covers, floor materials, floor mats, and back door panels.

[0068] As other uses of the deodorizing product of the present invention, the deodorizing fiber in particular can be used in textile products such as clothing such as underwear, socks, aprons, nursing clothing, futons, cushions, blankets, carpets, sofas, air filters (for example, filters for indoor or vehicle air conditioners, dehumidifiers, humidifiers, and air purifiers), futon covers, curtains, car seats, and other products processed with the deodorizing sheets described below.

[0069] As another application of the deodorizing product of the present invention, the deodorizing coating composition can be suitably used, for example, for the inner and outer walls of buildings, vehicles, railways, etc., waste incineration facilities, food waste containers, etc. In particular, it can be used for flooring and inner walls of factories with high VOC (volatile organic compounds) concentrations, and flooring and inner walls of fish markets.

[0070] The odor removing catalyst of the present invention and the deodorant composition and deodorant product containing the same have antibacterial and antiviral properties, and therefore can be used as an antibacterial and antiviral deodorant product. Specific uses are the same as those described above, and include, for example, upholstery, curtains, carpets, tiles, wallpaper, air filters (for example, filters for indoor or vehicle air conditioners, dehumidifiers, humidifiers, and air purifiers) and interior materials for vehicles, and suitable antibacterial and antiviral deodorant products can be used for these. EXAMPLES

[0071] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0072] [Example 1] 0.046 g of ruthenium (III) chloride (Sigma-Aldrich, purity: 45-55% as Ru), 1.52 g of cerium (III) nitrate hexahydrate (Fujifilm Wako Pure Chemical Industries, Ltd., purity: 98.0%), and 0.16 g of copper (II) nitrate trihydrate (Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.0%) were dissolved in 18 mL of distilled water. Next, 53 mL of 7 M aqueous sodium hydroxide solution was added to the obtained aqueous solution (hereinafter also referred to as "metal precursor aqueous solution") to generate a precipitate and stirred for 30 minutes. The obtained slurry was placed in a hydrothermal synthesis apparatus equipped with a 100 cc Teflon (registered trademark) inner cylinder and heated at 100 ° C for 24 hours. The slurry was filtered, and the residue (catalyst precursor) was washed with distilled water until the pH of the washing solution became constant, heated at 80 ° C for 24 hours to dry, and then calcined at 300 ° C for 2 hours under air flow to obtain catalyst A (odor removal catalyst A).

[0073] [Example 2] Catalyst B was obtained in the same manner as in Example 1, except that the amounts of ruthenium (III) chloride, cerium (III) nitrate hexahydrate, and copper (II) nitrate trihydrate were changed to 0.061 g, 1.52 g, and 0.49 g, respectively.

[0074] [Example 3] Catalyst C was obtained in the same manner as in Example 1, except that the amounts of ruthenium (III) chloride, cerium (III) nitrate hexahydrate, and copper (II) nitrate trihydrate were changed to 0.046 g, 0.76 g, and 0.58 g, respectively.

[0075] [Example 4] Catalyst D was obtained in the same manner as in Example 1, except that the amounts of ruthenium (III) chloride, cerium (III) nitrate hexahydrate, and copper (II) nitrate trihydrate were changed to 0.061 g, 0.51 g, and 1.06 g, respectively.

[0076] [Example 5] Catalyst E was obtained in the same manner as in Example 1, except that the amounts of ruthenium (III) chloride, cerium (III) nitrate hexahydrate, and copper (II) nitrate trihydrate were changed to 0.0091 g, 0.15 g, and 1.52 g, respectively.

[0077] [Example 6] Catalyst F was obtained in the same manner as in Example 1, except that the aqueous metal precursor solution was added to the aqueous sodium hydroxide solution.

[0078] [Example 7] Catalyst G was obtained in the same manner as in Example 1, except that copper (II) nitrate trihydrate was changed to 0.246 g of aluminum (III) nitrate nonahydrate.

[0079] [Example 8] Catalyst H was obtained in the same manner as in Example 1, except that copper (II) nitrate trihydrate was changed to 0.265 g of iron (III) nitrate nonahydrate.

[0080] [Example 9] Catalyst I was obtained in the same manner as in Example 1, except that copper (II) nitrate trihydrate was changed to 0.284 g of lanthanum (III) nitrate hexahydrate.

[0081] [Example 10] Catalyst J was obtained in the same manner as in Example 1, except that copper (II) nitrate trihydrate was changed to 0.0394 g of anhydrous silica.

[0082] [Example 11] Catalyst K was obtained in the same manner as in Example 1, except that an aqueous metal precursor solution was prepared by dissolving 0.046 g of ruthenium (III) chloride, 1.52 g of cerium (III) nitrate hexahydrate, 0.079 g of copper (II) nitrate trihydrate, and 0.123 g of aluminum (III) nitrate nonahydrate in 18 mL of distilled water.

[0083] [Example 12] Catalyst L was obtained in the same manner as in Example 11, except that aluminum nitrate (III) nonahydrate was changed to 0.132 g of iron nitrate (III) nonahydrate.

[0084] [Example 13] Catalyst M was obtained in the same manner as in Example 11, except that aluminum nitrate (III) nonahydrate was changed to 0.142 g of lanthanum nitrate (III) hexahydrate.

[0085] [Example 14] Catalyst N was obtained in the same manner as in Example 11, except that aluminum nitrate (III) nonahydrate was changed to 0.0197 g of anhydrous silica.

[0086] [Comparative Example 1] Catalyst G was obtained in the same manner as in Example 1, except that the amounts of ruthenium (III) chloride, cerium (III) nitrate hexahydrate, and copper (II) nitrate trihydrate used were changed to 0.061 g, 0.10 g, and 1.28 g, respectively.

[0087] [Comparative Example 2] Catalyst H was obtained in the same manner as in Example 1, except that ruthenium (III) chloride was not added, and the amounts of cerium (III) nitrate hexahydrate and copper (II) nitrate trihydrate used were changed to 1.52 g and 0.15 g, respectively.

[0088] [Comparative Example 3] Catalyst I was obtained in the same manner as in Example 1, except that copper (II) nitrate hexahydrate was not added, and the amounts of ruthenium (III) chloride and cerium (III) nitrate hexahydrate used were changed to 0.047 g and 1.52 g, respectively.

[0089] compositional analysis; The composition of the catalysts produced in each of the Examples and Comparative Examples (the ratio (mol%) of each metal atom to the total (100 mol%) of each metal atom) was confirmed by X-ray fluorescence analysis (XRF) using a wavelength dispersive X-ray fluorescence analyzer ZSX Primus IV (Rigaku Corporation). The results are shown in Table 1.

[0090] Evaluation of odor removal ability; 4 mg of the catalyst produced in each Example or Comparative Example was placed in a 3 L sampling bag, and 3 L of air was introduced. Then, propionaldehyde was introduced so that the propionaldehyde concentration was 1 ppm, and the bag was left at room temperature for 24 hours to conduct the deodorization test. The odor was evaluated using a handy odor monitor OMX-TDM (Shin-Ei Technology Co., Ltd.), and the degree of removal was determined according to the following formula. The results are shown in Table 1. Removal rate (%) = 100 - (sensor value after deodorization test / sensor value when blank (propionaldehyde 1 ppm)) x 100

[0091] [Table 1]

[0092] Continuous degradation test; [Example 15] A continuous decomposition test was carried out as follows, in which 10 mg of the odor removing catalyst A obtained in Example 1 was used in a fixed bed flow system to continuously treat a gas containing propionaldehyde as an odorant.

[0093] 10 mg of odor removal catalyst A was placed in a reaction tube, and a 10 ppm propionaldehyde mixed gas (diluted with air) was passed through at 3 L / h at 40°C or 80°C. The reaction tube inlet and outlet gases were introduced into a GC-MS to analyze the propionaldehyde concentration and carbon dioxide concentration. The GC-MS analysis was performed under the conditions shown in Table 2.

[0094] [Table 2]

[0095] From the analysis results, Figure 1 shows a graph indicating the change in propionaldehyde concentration over time, and Figure 2 shows a graph indicating the change in carbon dioxide concentration over time during the propionaldehyde continuous decomposition test. Figure 1 shows that the propionaldehyde concentration is steadily decreasing, and Figure 2 shows that carbon dioxide is being generated continuously, demonstrating that odor removal catalyst A can continuously remove propionaldehyde (aldehydes), an odorous substance, over a long period of time.

[0096] [Example 16] A continuous decomposition test was carried out as follows, in which 10 mg of the odor removal catalyst A obtained in Example 1 was used to continuously treat a gas containing ethyl acetate as an odorant in a fixed bed flow system. 10 mg of odor removal catalyst A was placed in a reaction tube, and 10 ppm ethyl acetate mixed gas (air diluted) was passed through at 3 L / h at 80°C. The reaction tube inlet and outlet gases were introduced into a GC-MS to analyze the ethyl acetate concentration and carbon dioxide concentration. The GC-MS analysis was performed under the conditions shown in Table 2. From the analysis results, Figure 3 shows a graph indicating the change in ethyl acetate concentration over time, and Figure 4 shows a graph indicating the change in carbon dioxide concentration over time during the ethyl acetate continuous decomposition test. Figure 3 shows that the ethyl acetate concentration is steadily decreasing, and Figure 4 shows that carbon dioxide is being generated continuously, demonstrating that odor removal catalyst A can continuously remove ethyl acetate (esters), an odorous substance, over a long period of time.

[0097] [Example 17] Deodorizing performance evaluation (propionaldehyde); 10 mg of the odor removal catalyst A obtained in Example 1 was placed in a 2L sampling bag (Frec Sampler, manufactured by Omi Odor Air Service Co., Ltd.). 1.5 L of air passed through an activated carbon filter was introduced into the 2L sampling bag, and a silicone cap was placed on the inlet. Next, 1 mL of 1500 vol. ppm propionaldehyde / air was injected into the sampling bag using a gas-tight syringe, and the propionaldehyde concentration in the sampling bag was adjusted to about 1 ppm. The odor intensity was sensorily evaluated after leaving the sample at rest for 1 hour, 5 hours, or 24 hours at room temperature.

[0098] Odor intensity is a numerical index of the degree of odor shown in Table 3 below. For the sensory evaluation, samples of each odor intensity were prepared and evaluated based on the relationship between propionaldehyde concentration and odor intensity shown in the graph (Figure 5) based on the relationship between the concentration of each odorous substance and odor intensity (http: / / kjknpo.com / html#j / bukai / kuki / qa / a11.htm) by the Air Environment Division of the Japan Healthy Housing Association. The sensory evaluation results are shown in Table 4.

[0099] [Table 3]

[0100] [Comparative Example 4] The same procedure as in Example 17 was carried out, except that the odor removing catalyst A was changed to 10 mg of coconut shell activated carbon (manufactured by Nacalai Tesque, Inc.). The sensory evaluation results are shown in Table 4.

[0101] [Comparative Example 5] The same procedure as in Example 17 was carried out, except that odor removing catalyst A was not used. The results of the sensory evaluation are shown in Table 4.

[0102] [Table 4]

[0103] [Example 18] Evaluation of odor return due to temperature increase; 10 mg of the odor removal catalyst A obtained in Example 1 was placed in a 2L sampling bag (Frec Sampler, manufactured by Omi Odor Air Service Co., Ltd.). 1.5 L of air passed through an activated carbon filter was introduced into a 2.0L sampling bag, and a silicone cap was placed on the inlet. Next, 1 mL of 1500 vol. ppm propionaldehyde / air was injected into the sampling bag using a gas-tight syringe, and the propionaldehyde concentration in the sampling bag was adjusted to about 1 ppm. The odor intensity was 0 when left to stand for 2 days at 20°C. The sampling bag was placed in an oven as it was, heated to 40°C, and left to stand for 1 hour, after which a sensory evaluation was performed. Thereafter, the same evaluation was performed at 60°C and 80°C. The results are shown in Table 5.

[0104] [Comparative Example 6] A sensory evaluation was carried out in the same manner as in Example 18, except that the odor removing catalyst A was changed to 10 mg of coconut shell activated carbon (manufactured by Nacalai Tesque, Inc.). The results are shown in Table 5.

[0105] [Comparative Example 7] A sensory evaluation was carried out in the same manner as in Example 18, except that odor removing catalyst A was not used. The results are shown in Table 5.

[0106] [Table 5]

[0107] [Example 19] Deodorizing performance evaluation (normal butyric acid); The same procedure as in Example 7 was carried out, except that in Example 17, 1 mL of propionaldehyde / air was used instead of 1 mL of normal butyric acid / air. The results of the sensory evaluation of odor intensity are shown in Table 6. The odor intensity was evaluated by preparing samples of each odor intensity based on the relationship between normal butyric acid concentration and odor intensity shown in Figure 5, and comparing them.

[0108] [Comparative Example 8] The same procedure as in Example 19 was carried out, except that the odor removing catalyst A was changed to 10 mg of coconut shell activated carbon (manufactured by Nacalai Tesque, Inc.). The sensory evaluation results are shown in Table 6.

[0109] [Comparative Example 9] The same procedure as in Example 19 was carried out, except that odor removing catalyst A was not used. The results of the sensory evaluation are shown in Table 6.

[0110] [Table 6]

[0111] [Example 20] Deodorizing composition containing a chemical adsorbent and evaluation of its deodorizing performance (trimethylamine); 5 mg of the odor removal catalyst A obtained in Example 1, 2.5 mg of the chemical adsorbent Kesmon NS-10 (manufactured by Toagosei) and 2.5 mg of Kesmon NS-70 (manufactured by Toagosei) were placed in a 3 L sampling bag (Frec Sampler, manufactured by Omi Odor Air Service Co., Ltd.) as a deodorant composition, 2.5 L of air was introduced, and a silicone cap was placed on the inlet. Next, 4.1 mL of 10,000 vol. ppm trimethylamine / air was injected into the sampling bag using a gas-tight syringe, and the triethylamine concentration in the bag was adjusted to about 15 ppm. The trimethylamine concentration after standing for 24 hours at 80°C was evaluated using a 180 L detector tube (manufactured by Gastec Co., Ltd.). A similar evaluation was performed without the odor removal catalyst as a blank, and the relative concentration, with the blank value taken as 100%, was 20%.

[0112] [Comparative Example 10] The same procedure as in Example 20 was carried out, except that the deodorant composition was changed to 10 mg of coconut shell activated carbon (manufactured by Nacalai Tesque, Inc.). As a blank, a similar evaluation was carried out without adding the odor removal catalyst, and the relative concentration, taking the blank value as 100%, was 60%.

[0113] [Example 21] Production of binder 1 In a reaction vessel equipped with a stirrer, reflux condenser, dropping device, and thermometer, 550g of ion-exchanged water and 1g of sodium dodecyl diphenyl ether disulfonate were charged, and the temperature was raised to 72°C while stirring and replacing with nitrogen. The internal temperature was kept at 72°C, and 3g of potassium persulfate was added as a polymerization initiator. After dissolution, an emulsion was prepared by adding 15g of acrylamide, 590g of methyl methacrylate, 330g of n-butyl acrylate, 20g of 2-hydroxyethyl methacrylate, 20g of methacrylic acid, 15g of ethylene glycol dimethacrylate, and 1g of t-dodecyl mercaptan to 400g of ion-exchanged water and 3g of sodium dodecyl diphenyl ether disulfonate under stirring, and the emulsion was continuously dropped into the reaction solution over 4 hours. After the dropwise addition, the mixture was aged for 2 hours. The obtained aqueous solution containing Binder 1 was cooled to room temperature, and then ion-exchanged water and an aqueous ammonium solution were added thereto to adjust the solid content to 50% by mass and the pH to 7.5, thereby obtaining a 50% by mass aqueous solution of Binder 1.

[0114] Coating solution preparation / coating (production of coating film N1) 3 g of the odor removal catalyst A obtained in Example 1, 6 g of a 50 mass% aqueous solution of binder 1, 3 g of a 5 mass% aqueous solution of thickener SN615 (manufactured by San Nopco Ltd.), 2 g of a 10 mass% aqueous solution of DOWFAX2A1 (manufactured by Dow Ltd.), and 13 g of water were mixed and stirred to obtain a coating liquid in which particles were uniformly dispersed. Using an applicator with a slit width of 40 μm and an auto film applicator (manufactured by Tester Sangyo Co., Ltd.), the coating liquid was applied onto a PET film (manufactured by Toyobo Co., Ltd., thickness 25 μm), and then dried at 80° C. for 10 minutes to obtain a coating film N1 in which particles were uniformly dispersed. The coating amount was 4.2 g / m 2 The coating amount of odor removal catalyst A was 2.0 g / m 2 It was.

[0115] [Example 22] Manufacturing of binder 2 In a reaction vessel equipped with a stirrer, reflux condenser, dropping device, and thermometer, 1000g of ion-exchanged water and 0.5g of sodium dodecyl diphenyl ether disulfonate were charged, and the temperature was raised to 75°C while stirring and replacing with nitrogen. The internal temperature was kept at 75°C, and 4g of ammonium persulfate was added as a polymerization initiator. After dissolution, an emulsion was prepared by adding 7g of acrylamide, 690g of styrene, 6g of divinylbenzene, and 15g of acrylic acid to 300g of ion-exchanged water and 3.5g of sodium dodecyl diphenyl ether disulfonate under stirring, and the emulsion was continuously dropped into the reaction solution over 4 hours. After the dropwise addition, the mixture was aged for 2 hours. The obtained aqueous solution containing binder 2 was cooled to room temperature, and then ion-exchanged water and an aqueous ammonium solution were added to adjust the solid content to 35% by mass and the pH to 8.0, to obtain a 35% by mass aqueous solution of binder 2.

[0116] Coating fluid preparation and coating (production of coated nonwoven fabric N2) 3.6 g of the odor removal catalyst A obtained in Example 1, 6.8 g of a 35 mass% aqueous solution of Binder 2, 6.2 g of a 5 mass% aqueous solution of Thickener SN615 (manufactured by San Nopco Ltd.), 2.4 g of a 10 mass% aqueous solution of DOWFAX2A1 (manufactured by Dow Ltd.), and 62 g of water were mixed and stirred to obtain a coating liquid in which the particles were uniformly dispersed. The obtained coating liquid was poured into a metal tray, and an A5 size (148 x 210 mm) PET nonwoven fabric (05TH-80, manufactured by Hirose Paper Co., Ltd.) was immersed for 2 minutes. Excess coating liquid was squeezed out with a squeezer, and the fabric was dried by heating at 80°C for 10 minutes to obtain coated nonwoven fabric N2 with particles uniformly dispersed therein. The coating amount was 2.9 g / m 2 The coating amount of odor removal catalyst A was 1.6 g / m 2 It was.

[0117] [Example 23] Coating fluid preparation and coating (production of coated nonwoven fabric N3) 9 g of the odor removal catalyst A obtained in Example 1, 6 g of an 8 mass % polyvinyl alcohol (Mw=60000, Mw / Mn=8) aqueous solution, and 9 g of water were mixed and stirred to obtain a coating liquid in which particles were uniformly dispersed. The coating liquid was applied to a PET nonwoven fabric (05TH-80, Hirose Paper Co., Ltd.) using an applicator with a slit width of 40 μm and an auto film applicator (Tester Sangyo Co., Ltd.), and then dried at 80° C. for 10 minutes to obtain a coated nonwoven fabric N3 in which particles were uniformly dispersed. The coating amount was 60.7 g / m 2 The coating weight of odor removal catalyst A was 57.6 g / m 2 , 42% by weight.

[0118] [Example 24] Deodorizing performance evaluation (acetaldehyde); 3 mg of the odor removal catalyst A obtained in Example 1 was placed in a 3 L sampling bag (Frec Sampler, manufactured by Omi Odor Air Service Co., Ltd.), 2.5 L of air that had been filtered through an activated carbon filter was introduced, and a silicone cap was placed on the inlet. Next, 1 mL of acetaldehyde / air at 2500 vol. ppm was injected into the sampling bag using a gas-tight syringe, and the acetaldehyde concentration in the bag was adjusted to about 1 ppm. The odor intensity was evaluated by sensory evaluation after leaving the bag at 40°C for 24 hours. The evaluation results are shown in Table 7. The odor intensity was evaluated by preparing samples of each odor intensity based on the relationship between acetaldehyde concentration and odor intensity shown in Figure 5, and comparing them.

[0119] [Example 25] Deodorizing performance evaluation (acetaldehyde / coated film N1); 15 cm of the coating film N1 produced in Example 21, equivalent to 3 mg of odor removal catalyst A 2 In the odor eliminating performance evaluation of Example 24, the coated film N1 was cut out to 15 cm instead of the odor eliminating catalyst A. 2 Except for using the above, the deodorizing performance against acetaldehyde was evaluated in the same manner as in Example 24. The evaluation results are shown in Table 7.

[0120] [Example 26] Deodorizing performance evaluation (acetaldehyde / coated nonwoven fabric N2); The coated nonwoven fabric N2 produced in Example 22 had a thickness of 18.8 cm, which corresponds to 3 mg of odor removal catalyst A. 2 In the odor eliminating performance evaluation of Example 24, the coated nonwoven fabric N2 was cut out in place of the odor eliminating catalyst A. 2 The deodorizing performance against acetaldehyde was evaluated in the same manner as in Example 24, except that the above was used. The evaluation results are shown in Table 7.

[0121] [Example 27] Deodorizing performance evaluation (acetaldehyde / coated nonwoven fabric N3); 0.5 cm2 of the coated nonwoven fabric N3 produced in Example 23, equivalent to 3 mg of odor removal catalyst A 2 In the odor eliminating performance evaluation of Example 24, 0.5 cm of the coated nonwoven fabric N2 was cut out instead of the odor eliminating catalyst A. 2 The deodorizing performance against acetaldehyde was evaluated in the same manner as in Example 24, except that the above was used. The evaluation results are shown in Table 7.

[0122] [Comparative Example 11] The same procedure as in Example 24 was carried out, except that odor removing catalyst A was not used. The results of the sensory evaluation are shown in Table 7.

[0123] [Table 7]

[0124] [Example 28] Deodorizing performance evaluation (formaldehyde); The same procedure as in Example 24 was carried out, except that instead of adjusting the acetaldehyde concentration in the bag to about 1 ppm, the formaldehyde concentration in the bag was adjusted to about 10 ppm. The sensory evaluation results are shown in Table 8. The odor intensity was evaluated by preparing samples of each odor intensity based on the relationship between formaldehyde concentration and odor intensity shown in Figure 5, and comparing them.

[0125] [Example 29] Deodorizing performance evaluation (formaldehyde / coated film N1); The same procedure as in Example 25 was carried out, except that the formaldehyde concentration in the bag was adjusted to about 10 ppm instead of the acetaldehyde concentration in the bag of Example 25. The sensory evaluation results are shown in Table 8.

[0126] [Example 30] Deodorizing performance evaluation (formaldehyde / coated nonwoven fabric N3); The same procedure as in Example 27 was carried out, except that the formaldehyde concentration in the bag was adjusted to about 10 ppm instead of the acetaldehyde concentration in the bag of Example 27. The sensory evaluation results are shown in Table 8.

[0127] [Comparative Example 12] The same procedure as in Example 28 was carried out, except that odor removing catalyst A was not used. The results of the sensory evaluation are shown in Table 8.

[0128] [Table 8]

[0129] [Example 31] Deodorizing performance evaluation (propionaldehyde); The same procedure as in Example 24 was carried out, except that instead of adjusting the acetaldehyde concentration in the bag to about 1 ppm, the propionaldehyde concentration in the bag was adjusted to about 1 ppm. The sensory evaluation results are shown in Table 9. The odor intensity was evaluated by preparing samples of each odor intensity based on the relationship between propionaldehyde concentration and odor intensity shown in Figure 5, and comparing them.

[0130] [Example 32] Deodorizing performance evaluation (propionaldehyde / coated film N1); The same procedure as in Example 25 was carried out, except that instead of adjusting the acetaldehyde concentration in the bag to about 1 ppm, the propionaldehyde concentration in the bag was adjusted to about 1 ppm. The sensory evaluation results are shown in Table 9.

[0131] [Example 33] Deodorizing performance evaluation (propionaldehyde / coated nonwoven fabric N2); The same procedure as in Example 26 was carried out, except that instead of adjusting the acetaldehyde concentration in the bag to about 1 ppm, the propionaldehyde concentration in the bag was adjusted to about 1 ppm. The sensory evaluation results are shown in Table 9.

[0132] [Example 34] Deodorizing performance evaluation (propionaldehyde / coated nonwoven fabric N3); The same procedure as in Example 27 was carried out, except that instead of adjusting the acetaldehyde concentration in the bag to about 1 ppm, the propionaldehyde concentration in the bag was adjusted to about 1 ppm. The sensory evaluation results are shown in Table 9.

[0133] [Comparative Example 13] The same procedure as in Example 31 was carried out, except that odor removing catalyst A was not used. The results of the sensory evaluation are shown in Table 9.

[0134] [Table 9]

[0135] [Example 35] Antibacterial evaluation; Antibacterial evaluation was performed using Staphylococcus aureus NBRC12732 and Escherichia coli NBRC3301 in accordance with JIS L1902. The test bacteria solution was 1 / 20 nutrient broth medium, and the bacterial concentration was 1.5 x 10 5 (CFU / mL) was used. A standard cotton cloth was used as a control.

[0136] 0.4 g of the coated nonwoven fabric N3 obtained in Example 23 was placed in a vial, 0.2 ml of the test bacteria liquid was dropped onto the coated nonwoven fabric N3, the vial was then capped, and cultured at 37°C for 18 hours. The test bacteria were washed out from the test piece, and the live bacteria in the washed out liquid were cultured using normal agar medium, and the number of E. coli colonies was counted (pour plate culture method). The same procedure was repeated three times, and the average values ​​are shown in Tables 10 and 11. The antibacterial activity value was calculated using the following formula. An antibacterial activity value of ≧2.0 is judged to have antibacterial properties.

[0137] Antibacterial activity value = [Log (control sample · viable bacteria count after incubation) - Log (control sample · viable bacteria count immediately after inoculation)] - [Log (test sample · viable bacteria count after incubation) - Log (test sample · viable bacteria count immediately after inoculation)]

[0138] [Comparative Example 14] Antibacterial evaluation was carried out in the same manner as in Example 35, except that a nonwoven fabric (05TH-80, manufactured by Hirose Paper Co., Ltd.) was used instead of the coated nonwoven fabric N3. The results are shown in Tables 10 and 11.

[0139] [Table 10]

[0140] [Table 11] [Industrial Applicability]

[0141] The odor removal catalyst, deodorant composition, and deodorant product of the present invention can be suitably used to reduce and remove odors caused by odorous substances in the air, and can be particularly suitably used for deodorizing indoors, such as the inside of a car. The odor removal catalyst, deodorant composition, and deodorant product of the present invention may be used as is, or may be combined with other materials such as resins and used for applications such as resin coating materials, interior sheet materials, and automobile inner panels. In addition, the odor removal catalyst, deodorant composition deodorant product of the present invention, and antibacterial and antiviral deodorant products containing the odor removal catalyst or deodorant composition of the present invention can be applied to various applications without particular restrictions, and can be applied to, for example, upholstery, curtains, carpets, tiles, wallpaper, air filters, or vehicle interior materials.

Claims

1. A first metal element, At least one second metallic element selected from the group consisting of Al, Si, Fe, and Cu; and C.E. a ratio of the atoms of the first metal element to the total of the atoms of the first metal element, the atoms of the second metal element, and Ce atoms is 1 to 5 mol %, a ratio of the atoms of the second metal element is 15 to 75 mol %, and a ratio of Ce atoms is 20 to 80 mol %, An odor removal catalyst, wherein the first metal element is Ru.

2. An odor removal catalyst as described in claim 1, wherein the second metal element is Cu.

3. A deodorant composition comprising the odor removing catalyst according to claim 1 or 2 and a chemical adsorbent.

4. A deodorizing product comprising the odor removing catalyst according to claim 1 or 2 or the deodorizing composition according to claim 3.

5. 5. The deodorizing product according to claim 4, which is a deodorizing fiber, a deodorizing paint or a deodorizing sheet.

6. 6. A chair upholstery, a curtain, a carpet, a tile, a wallpaper, an air filter, or an interior material for a vehicle, which uses the deodorizing product according to claim 4 or 5.

7. An antibacterial and antiviral deodorizing product comprising the odor removing catalyst according to claim 1 or 2 or the deodorant composition according to claim 3.

8. 8. The antibacterial and antiviral deodorizing product according to claim 7, which is used for upholstery, curtains, carpets, tiles, wallpaper, air filters, or interior materials for vehicles.

Citation Information

Patent Citations

  • JP1986118627U

  • Cleaning catalyst at normal temperature and utilization thereof

    JP2001187343A

  • Gas removing material and method for producing the same

    JP2003159315A

  • Deodorizer, its manufacture method, and deodorizing filter

    JP2008104845A

  • Air cleaning catalyst and its manufacturing method

    JP2010131531A